Representation of the ecological crisis impact in Sumur, a short story written by Eka Kurniawan - Setiyoningsih, Titi; Suwandi, Sarwiji; Wardani, Nugraheni E.; Ulya, Chafit; Setyawan, Eko; Zulianto, Sugit (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2024)
The ecological crisis is getting worse over time, resulting in various problems. The ecological crisis is widely represented in literary works but not much has been studied regarding its impact so it needs to be explained in depth. This study aimed to describe the impact of the ecological crisis represented in “Sumur”, a short story by Eka Kurniawan. The data of this research were words, phrases, clauses, sentences, paragraphs, and discourse in the short story. The data collection technique was a document analysis using the theory of ecocriticsm. The data validity technique used theoretical triangulation through data validity activities based on various theoretical perspectives. The novelty of the research was that no one had previously analyzed the ecocriticism in the short story before. The data analysis technique used interactive analysis. The findings indicated that the impact of the ecological crisis represented in "Sumur" short story included: 1) the effects on the environment in the form of drought, loss of water sources, loss of animal food and habitat, damage to agriculture, climate change, and damage to biodiversity; and 2) the effects on the socio-cultural relations of the community in the form of death and anxiety, population migration and urbanization, and the loss of community culture.